Determination of qualified human resources using the ANFIS method - Amri , Ahmad Alfauzan; Roshan, Rohit; Ananda, Debby; Tarigan, Richard Fernando; Wong, Yano Sabar M; Turnip, Mardi (Sinkron : jurnal dan penelitian teknik informatika, 2023)
To improve the quality of education is very closely related to the problem of human resources. One of the main key in creating professional human resource lies in the recruitment process, workforce selection and training. Finding a professional and qualified workforce is not easy and a must in an organization or university in screening new employees or lecturers. Therefore we need a system for organizations and universities to be able to get the right people, qualified and placed according to their abilities. This research was conducted using quantitative descriptive research methods and data collection methods in the form of questionnaires and using Adaptive Neuro-Fuzzy Inference System (ANFIS). From the results of testing the data this algorithm shows a data accuracy rate of 77 percent Keywords: HR, ANFIS, questionnaire, quantitative description